A Cell Type Independent Binary Grading System Does Not Significantly Improve Endometrial Biopsy Interpretation. (May 2016) - Nastic, Denis; Kahlin, Frida; Dahlstrand, Hanna; Carlson, Joseph W.
Abstract : The revised International Federation of Gynecology and Obstetrics (FIGO) grading system is widely accepted as the standard in evaluating endometrial carcinoma on biopsy. Determination of tumor cell type [using the World Health Organization (WHO) diagnostic criteria] and grade (using FIGO) guides surgical approach. Several studies have highlighted discrepancies between biopsy and hysterectomy diagnosis. Recently, a binary grading system was proposed, yielding a low-risk and high-risk assessment but in a cell type independent (CTI) way. No study has assessed its utility in biopsy grading, a situation where this system may be particularly useful. Archived endometrial biopsies from 70 cases of endometrial carcinoma were graded by 3 independent observers using the WHO/FIGO and the CTI grading systems. The overall accuracy, interobserver agreement, and ease of use were assessed. This study found comparable substantial accuracy between the WHO/FIGO and CTI grading systems (κ=0.71 vs. κ=0.69), with the same setbacks in overgrading of 20.9% versus 25.6% of low-risk tumors. The CTI grading system was not superior to the WHO/FIGO grading system in accuracy of subtyping and grading and interobserver reproducibility. Although determination of cell type is difficult, it does not appear that the proposed CTI system confers any significant advantages over existing grading.